A cold day in Paradise - Hamilton, Steve, 1961- (Hamilton, Steve, 1961- Alex McKnight novel., 2012)
As ex-Detroit cop Alex McKnight searches for the killer of a bookmaker, he begins to receive a series of mysterious and ominous messages, seemingly from a man imprisoned for life for the murder of Alex's former partner.